INVERSE MODELING APPROACH FOR OBTAINING KINETIC PARAMETERS OF DIFFUSION-CONTROLLED METAMORPHIC REACTIONS IN THE KHARLOVO CONTACT AUREOLE (SOUTH SIBERIA, RUSSIA) - Likhanov I.I.; Ananiev V.A.; Reverdatto V.V.; Ten A.A.; Memmi I. (My University, 2001)
A new approach for deriving kinetic parameters of diffusion-controlled metamorphic reactions is described. It is based on comparison of models of temperature field evolution near a cylindrical intrusion and observable chemical changes in biotite at the contact aureole of the Kharlovo massif. Unlike other methods used to construct quantitative models of reactions which produce distinctly expressed zoned microtextures, the proposed approach allows better understanding of the processes occurring in texture-homogeneous rocks, where complete consumption of some reactant mineral phases prevent accurate reconstruction of the metamorphic process. The calculations yielded estimates of the effective rates of metamorphic reactions (10-12 s-1) and the effective diffusion coefficient (5.29 × 10-16 cm2 s-1). These values are consistent with experimentally and theoretically derived estimates of solid-state diffusion, including grain-boundary diffusion.